Os perigos do conceito de impacto no ensino superior (The dangers of the concept of impact in higher education) - McCowan, Tristan (Revista Eletrônica de Educação, 2019)
The impact of higher education institutions on society has become the focus of significant policy attention in recent years, most prominently as part of research evaluation. This paper presents a theoretical exploration of the notion, identifying the key dimensions as source, form, trajectory, intensity, timescale and destination. While acknowledging the importance of porosity between universities and society, and the need to address critical contemporary challenges, five dangers of the impact agenda are highlighted: the normative dimension; the linear relationship; unpredictability; measurement; and instrumentalization. As a response to dominant conceptualizations, the paper proposes the notion of the generative intrinsic as a more robust basis on which to base the work of universities. Resumo O impacto das instituições de ensino superior na sociedade tem se tornado o foco de atenção política significativa nos últimos anos, mais proeminentemente como parte da avaliação da pesquisa. Este artigo apresenta uma exploração teórica da categoria noção, identificando as dimensões-chave como fonte, forma, trajetória, intensidade, escala de tempo e destino. Embora reconhecendo a importância da porosidade entre as universidades e a sociedade, e a necessidade de abordar desafios contemporâneos críticos, cinco perigos da agenda de impacto são destacados: a dimensão normativa; o relacionamento linear; imprevisibilidade; medição; e instrumentalização. Como resposta às conceituações dominantes, o artigo propõe a noção do intrínseco generativo como uma base mais robusta sobre a qual basear o trabalho das universidades. Keywords: Higher education policy, Impact, Instrumentalization, Public engagement, Research evaluation, Universities. Palavras-chave: Políticas de educação superior, Impacto, Instrumentalização, Engajamento público, Avaliação da pesquisa, Universidades. References ASHWIN, P. (2016) ‘From a teaching perspective, “impact” looks very different’. Times Higher Education, 21 March. Online. www.timeshighereducation.com/blog/teaching-perspectiveimpact-looks-very-different (accessed 3 May 2018). BARNETT, R. (2004) ‘The purposes of higher education and the changing face of academia’. London Review of Education, 2 (1), 61–73. BELFIORE, E. (2014) ‘”Impact”, “value” and “bad economics”: Making sense of the problem of value in the arts and humanities’. Arts and Humanities in Higher Education, 14 (1), 95–110. BRENNAN, J., KING, R. AND LEBEAU, Y. (2004) The Role of Universities in the Transformation of Societies: Synthesis report. London: Association of Commonwealth Universities and the Open University BYNNER, J. AND EGERTON, M. (2001) The Wider Benefits of Higher Education. Report by the Wider Benefits of Learning Research Centre, Institute of Education, University of London. CHUBB, J. AND WATERMEYER, R. (2017) ‘Artifice or integrity in the marketization of research impact? Investigating the moral economy of (pathways to) impact statements within research funding proposals in the UK and Australia’. Studies in Higher Education, 42 (12), 2,360–72. COLEMAN, J.S. (1986) ‘The idea of the developmental university’. Minerva: A Review of Science, Learning and Policy, 24 (4), 476–94. COLLINI, S. (2012) What are Universities For? London: Penguin. Dewey, J. (1967) ‘The continuum of ends-means’. In Archambault, R. (ed.) John Dewey on Education: Selected writings. Chicago: University of Chicago Press, 97–107. ESRC (Economic and Social Research Council) (n.d.) ‘What is impact?’. Online. www.esrc.ac.uk/ research/impact-toolkit/what-is-impact/ (accessed 22 April 2018). FIELDING, M. (2003) ‘The impact of impact’. Cambridge Journal of Education, 33 (2), 289–95. FRANCIS, B. (2011) ‘Increasing impact? An analysis of issues raised by the impact agenda in educational research’. Scottish Educational Review, 43 (2), 4–16. GIBBONS, M., LIMOGES, C., NOWOTNY, H., SCHWARTZMAN, S., SCOTT, P. AND TROW, M. (1994) The New Production of Knowledge: The dynamics of science and research in contemporary societies. London: SAGE Publications. GUNN, A. AND MINTROM, M. (2016) ‘Higher education policy change in Europe: Academic research funding and the impact agenda’. European Education, 48 (4), 241–57. GUNN, A. AND MINTROM, M. (2017) ‘Five things to consider when designing a policy to measure research impact’. The Conversation, 12 January. Online. http://theconversation.com/fivethings-to-consider-when-designing-a-policy-to-measure-research-impact-71078 (accessed 22 April 2017). ILIE, S. AND ROSE, P. (2016) ‘Is equal access to higher education in South Asia and sub-Saharan Africa achievable by 2030?’. Higher Education 72 (4), 435–55. JUMP, P. (2015) ‘The impact of impact’. Times Higher Education, 19 February. Online. www.timeshighereducation.com/features/the-impact-of-impact/2018540.article (accessed 3 May 2018). LEE, S.T. (2017) ‘The Structure of a University: A Karatanian interrogation into instrumentalism, idealism and community in postwar British higher education, 1945–2015’. Unpublished PhD thesis, Birkbeck University. MACFARLANE, B. (2011) ‘The morphing of academic practice: Unbundling and the rise of the paraacademic’. Higher Education Quarterly, 65 (1), 59–73. Marginson, S. (2011) ‘Higher education and public good’. Higher Education Quarterly, 65 (4), 411–33. MARGINSON, S. (2016) ‘The worldwide trend to high participation higher education: Dynamics of social stratification in inclusive systems’. Higher Education, 72 (4), 413–34. MARTIN, B. (2011) ‘The Research Excellence Framework and the ‘impact agenda’: Are we creating a Frankenstein monster?’. Research Evaluation, 20 (3), 247–54. MARTIN, C. (2011) ‘Philosophy of education in the public sphere: The case of “relevance”’. Studies in Philosophy and Education, 30, 615–29. McCowan, T. (2009) Rethinking Citizenship Education: A curriculum for participatory democracy. London: Continuum. MCCOWAN, T. (2015) ‘Should universities promote employability?’. Theory and Research in Education, 13 (3), 267–85. MCCOWAN, T. (2016a) ‘Three dimensions of equity of access to higher education’. Compare: A Journal of Comparative and International Education, 46 (4), 645–65. MCCOWAN, T. (2016b) ‘Universities and the post-2015 development agenda: An analytical framework’. Higher Education, 72 (4), 505–23. MCCOWAN, T. (2017) ‘Higher education, unbundling and the end of the university as we know it’. Oxford Review of Education, 43 (6), 733–48. McDowell, G. (2003) ‘Engaged universities: Lessons from the land-grant universities and extension’. The Annals of the American Academy of Political and Social Science, 585 (1), 31–50. MCMAHON, W. (2009) Higher Learning, Greater Good: The private and social benefits of higher education. Baltimore, MD: Johns Hopkins University Press. NIXON, J. (2004) ‘Education for the good society: The integrity of academic practice’. London Review of Education, 2 (3), 245–52. OANCEA, A. (2013a) ‘Buzzwords and values: The prominence of “impact” in UK research policy and governance’. Research Trends, 33, 6–8. OANCEA, A. (2013b) ‘Interpretations of research impact in seven disciplines’. European Educational Research Journal, 12 (2), 242–50. OKETCH, M., MCCOWAN, T. AND SCHENDEL, R. (2014) The Impact of Tertiary Education on Development: A rigorous literature review. London: Department for International Development. OVSEIKO, P., OANCEA, A. AND BUCHAN, A. (2012) ‘Assessing research impact in academic clinical medicine: A study using Research Excellence Framework pilot impact indicators’. BMC Health Services Research, 12 (478), 1–23. PARKER, J. AND VAN TEIJLINGEN, E. (2012) ‘The Research Excellence Framework (REF): Assessing the impact of social work research on society’. Practice: Social Work in Action, 24 (1), 41–52. PENFIELD, T., BAKER, M.J., SCOBLE, R. AND WYKES, M.C. (2014) ‘Assessment, evaluations, and definitions of research impact: A review’. Research Evaluation, 23 (1), 21–32. PERKIN, H. (2007) ‘History of universities’. In Forest, J.J.F. and Altbach, P.G. (eds) International Handbook of Higher Education. Dordrecht: Springer, 159–206. PHIPPS, A. (2014) ‘The dark side of the impact agenda’. Times Higher Education, 4 December. Online. www.timeshighereducation.com/comment/opinion/the-dark-side-of-the-impactagenda/2017299.article (accessed 3 May 3018). READINGS, B. (1996) The University in Ruins. Cambridge, MA: Harvard University Press. REF (Research Excellence Framework) (2011) Assessment Framework and Guidance on Submissions: Research excellence framework 02.2011. Online. www.ref.ac.uk/2014/pubs/2011-02/ (accessed 22 April 2018). RESEARCH COUNCIL ECONOMIC IMPACT GROUP (2006) Increasing the Economic Impact of Research Councils. London: Department of Trade and Industry. Research Councils UK (2017) Excellence with Impact. Online. www.ukri.org/innovation/excellencewith-impact/ (accessed 15 July 2017). SALL, E., LEBEAU, Y. AND KASSIMIR, R. (2003) ‘The public dimensions of the university in Africa’. Journal of Higher Education in Africa, 1 (1), 126–48. SANTOS, B.S. (2004) A universidade do século XXI: Para uma reforma democratica e emancipatória da universidade. São Paulo: Cortez. Siegfried, J., Sanderson, A. and McHenry, P. (2007) ‘The economic impact of colleges and universities’. Economics of Education Review, 26 (5), 546–58. SMITH, S., WARD, V. AND HOUSE, A. (2011) ‘”Impact” in the proposals for the UK’s Research Excellence Framework: Shifting the boundaries of academic autonomy’. Research Policy, 40 (10), 1,369–79. UNIVERSITIES UK (2014) The Impact of Universities on the UK Economy. London: Universities UK. UPTON, S., VALLANCE, P. AND GODDARD, J. (2014) ‘From outcome to process: Evidence for a new approach to research impact assessment’. Research Evaluation, 23 (4), 352–65. WALTER, I., NUTLEY, S.M. AND DAVIES, H.T.O. (2003) Research Impact: A cross-sector review. Research Unit for Research Utilisation, University of St Andrews. Online. www.ruru.ac.uk/pdf/LSDA%20 literature%20review%20final.pdf (accessed 22 April 2016). WATERMEYER, R. (2016) ‘Impact in the REF: Issues and obstacles’. Studies in Higher Education, 41 (2), 199–214. WEISS, C. (1979) ‘The many meanings of research utilization’. Public Administration Review, 39 (5), 426–31. WISSEMA, J.G. (2009) Towards the Third Generation University: Managing the university in transition. Cheltenham: Edward Elgar